Role of fetal head‐circumference‐to‐maternal‐height ratio in predicting Cesarean section for labor dystocia: prospective multicenter study. (3rd January 2023) - Dall'Asta, A.; Ramirez Zegarra, R.; Corno, E.; Mappa, I.; Lu, J. L. A.; Di Pasquo, E.; Morganelli, G.; Abou‐Dakn, M.; Germano, C.; Attini, R.; Masturzo, B.; Rizzo, G.; et al.
ABSTRACT: Objective: To evaluate the relationship between the fetal head‐circumference‐to‐maternal‐height (HC/MH) ratio measured shortly before delivery and the occurrence of Cesarean section (CS) for labor dystocia. Methods: This was a multicenter prospective cohort study involving four tertiary maternity hospitals. An unselected cohort of women with a singleton fetus in cephalic presentation, at a gestational age beyond 36 + 0 weeks and without any contraindication for vaginal delivery, was enrolled between September 2020 and November 2021. The MH and fetal HC were measured on admission of the patient to the labor ward. The primary outcome of the study was the performance of the HC/MH ratio in the prediction of CS for labor dystocia. Women who underwent CS for any indication other than failed labor progression, including fetal distress, were excluded from the final analysis. Results: A total of 783 women were included in the study. Vaginal delivery occurred in 744 (95.0%) women and CS for labor dystocia in 39 (5.0%). CS for labor dystocia was associated with shorter MH (mean ± SD, 160.4 ± 6.6 vs 164.5 ± 6.3 cm; P < 0.001), larger fetal HC (339.6 ± 9.5 vs 330.7 ± 13.0 mm; P < 0.001) and a higher HC/MH ratio (2.12 ± 0.11 vs 2.01 ± 0.10; P < 0.001) compared with vaginal delivery. Multivariate logistic regression analysis showed that the HC/MH ratio was associated independently with CS for labor dystocia (adjusted odds ratio, 2.65 (95% CI, 1.85–3.79); P < 0.001). The HC/MH ratio had an area under the receiver‐operating‐characteristics curve of 0.77 and an optimal cut‐off value for discriminating between vaginal delivery and CS for labor dystocia of 2.09, which was associated with a sensitivity of 0.62 (95% CI, 0.45–0.77), specificity of 0.79 (95% CI, 0.76–0.82), positive predictive value of 0.13 (95% CI, 0.09–0.19) and negative predictive value of 0.98 (95% CI, 0.96–0.99). Conclusions: In a large cohort of unselected pregnancies, the HC/MH ratio performed better than did fetal HC and MH alone in identifying those cases that will undergo CS for labor dystocia, albeit with moderate predictive value. The HC/MH ratio could assist in the evaluation of women at risk for CS for labor dystocia. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.